The synthesis of novel crown ethers, part IX, 3-phenyl chromenone-crown ethers - (:unkn) unknown (HETERO CORPORATION, 2001)
3-Phenyl- and 3-(p-methoxyphenyl)-7,8-dihydroxy and -6,7-dihydroxychromenones were prepared from ethyl 3-oxo-2-phenylpropanoate, ethyl 3-oxo-2-(4-methoxyphenyl)-propanoate and the trihydroxy benzenes in H2SO4. 3-Aryl-7,8- and 3-aryl-6,7-dihydroxy-2H-chromenones reacted with the bis-dihalides of polyglycols in DMF/MeCO3 to afford 12-Crown-4, 15-Crown-4 and 18-Crown-6-chromenones. The products were identified with IR, 1H NMR, low and high resolution mass spectroscopy and elemental analysis. Some 1: 1 cation association constants, K-b, of the 3-phenyl chromenone crown ethers with Li+, Na+, K+ and Rb+ cations were studied by steady state emission fluorescence spectroscopy; K-b chromenone-crown complexes displayed crown ether-cation binding selectivity rules properly in acetonitrile.
Keywords: FLUORESCENCE-SPECTRA; CATION-BINDING; COUMARIN DERIVATIVES; MACROCYCLES; RECOGNITION